Multiskalige Modellierung von Lithium-Ionen-Batterien - Schmidt, Adrian (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
In this work, model approaches for the internal processes of large-format lithium-ion batteries are developed, experimentally parameterized, and validated. The electrochemical losses in the electrode's microstructure are investigated as well as their interaction with the heterogeneous potential and temperature distribution of large-format cells. In addition, permissible operating conditions of the cells are identified as well as potentials with regard to increasing power and energy density.